Mosquito Eradication with Family Medicinal Plant Innovations (PERISAI TOGA) - Adisa Mahendra Putri, Diera; Tirana Herdiyansari, Finlandini; Marsyanti, Windy; Keisha Syahputri Nuradi, Elaine; Yosellanda Al Sabina, Della; Afrizal Setiawan, Raihan; Setyoputri, Marschela; Tiku Rerung, Gestia; Kamba, Ismail; Syamsir , Syamsir (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : PERISAI TOGA is an innovative program to eradicate mosquitoes by utilizing family medicinal plants, especially lemongrass, as a natural alternative. Lemongrass is known to be effective in repelling Aedes aegypti because it contains natural chemical compounds, specifically Citronellal and Geraniol, which can interfere mosquitoes by the smell of it. Objective : This research aims to increase community knowledge about the importance of mosquito eradication through the 3M Plus method, while also providing long-term solutions that can be managed by the residents themselves. One of the proposed solutions is the utilization of lemongrass to create products such as anti-mosquito spray and aromatherapy candles. Research Methods/ Implementation Methods : The sampling method used for this program was simple random sampling technique which was attended by 18 women of Family Welfare Empowerment. A Wilcoxon test was used to measure participants' knowledge levels after attending the program. Results : The results of the study showed a significant difference between the pre-test and post-test scores, with a p-value of 0.000 < α 0.05. The evaluation results indicated an increase in participants' knowledge after attending the counseling and demonstrations on the importance of mosquito eradication and the process of making lemongrass-based products. Conclusion/Lesson Learned : In conclusion, the counseling and demonstrations were effective in increasing community awareness about mosquito eradication and the use of lemongrass as a natural anti-mosquito alternative.